The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. - Domenech, Jordi; Orihuela, Ruben; Mir, Gisela; Molinas, Marisa; Atrian, Silvia; Capdevila, Merce (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.
Keywords: cadmium; Cadmium: chemistry; Cadmium–His binding; Drug; Glutathione; Metabolic Detoxication; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Phytochelatins; Plant metallothionein; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Protein Binding; Protein Conformation; Quercus; Recombinant Proteins; Sulfide ligands; yeast complementation

The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. - Domenech, Jordi; Orihuela, Ruben; Mir, Gisela; Molinas, Marisa; Atrian, Silvia; Capdevila, Merce (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.
The following values have no corresponding Zotero field: accession-num: 17503092
Keywords: cadmium; Cadmium: chemistry; Cadmium–His binding; Drug; Glutathione; Metabolic Detoxication; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Phytochelatins; Plant metallothionein; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Protein Binding; Protein Conformation; Quercus; Recombinant Proteins; Sulfide ligands; yeast complementation